India and Retailing -Two Promising Bandwagons of the New Millennium - Devgan , Deepak; Kaur, Mandeep (Gyan Management Journal, 2009)
This paper aims to get an insight into the prevailing scenario of organised retailing in India since the beginning of the new millennium. In addition, the pitper also makes an attempt to project the future prospects of organised retailing in India. This pqper is based on the secondary data pertaining to position of orgamsed retailing in India. The analysis revealed that organised retailing will remain the most sought after destination for retail giants in the times to come and likely to become one of the major contributors towards the GDP of India. However, the concentration of organised retailing in a few big cities and metros only has been found to be a matter of serious concern.
Keywords: India; New Millennium; Organised Retai; Retailing Scenario; Strategy Formation